Green Hotel Certification and Guest Perceptions: Sustainability Practices in Nepal’s Hospitality Sector - Gautam, Mandira; Niraula, Damodar (NPRC Journal of Multidisciplinary Research, 2025)
Background: The global hospitality sector is increasingly emphasizing sustainable tourism, with green certifications influencing traveler preferences. However, in Nepal, the adoption of formal certification systems is limited, and sustainable practices are often informal and unstructured.Objectives: This study examines the influence of green hotel practices and certifications on guest satisfaction in Nepal. It aims to synthesize global evidence on certification impacts and identify which sustainability practices are most visible and valued by guests in the Nepalese context.Methods: A qualitative, narrative synthesis approach was employed, analyzing global literature and TripAdvisor reviews from 20 certified and non-certified Nepalese hotels. Guest reviews were coded for keywords related to observable sustainability practices.Findings: Guest reviews in Nepal indicate that visible practices—such as organic and locally sourced food, energy efficiency, plastic reduction, and community support—are more strongly associated with satisfaction and positive perception than formal certifications alone. While certifications enhance credibility, tangible eco-friendly efforts are more directly appreciated and noticed by guests.Conclusion: For hotels in Nepal to remain competitive, they should integrate both visible sustainability practices and credible certifications. Strengthening policy support, industry awareness, and strategic guest communication is critical for advancing sustainable hospitality in the country.Novelty: This study provides the first integrated analysis of global certification literature and real guest feedback specific to Nepal’s hospitality sector, highlighting the distinct primacy of tangible practices over certification labels in shaping guest satisfaction in a developing economy.